Factors affecting positive and negative word of mouth in restaurant industry- A review - psgim, jcrm (Journal of Contemporary Research in Management (JCRM), 2023)
Word-of-mouth advertising is the thing that happens when a customer discusses about business with another person it’s either decidedly or contrarily. With regards to the restaurant industry, it is an unforgiving industry, and it’s a tuff business to be in. There is just a single shot in this industry, do or kick the bucket. In this research, we’d have to discuss the impact in both courses on the restaurant industry. The thoughts about that was, the subject talks a great deal, the "restaurant industry" is so colossal, and dubious, as a result of the excursions of stages. Diverse cooking styles, Different sorts, some might be fast-food while the other is a semi- formal restaurant, and the list goes on. The findings of the research reveals that positive word of mouth impacts more on customers and that too based on factors like quality, characteristics, price etc. Though promotional activities of a brand influence customer’s mind, word of mouth stimulates more personally.